2019
DOI: 10.1016/j.chemosphere.2018.12.178
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory marker and aryl hydrocarbon receptor-dependent responses in human macrophages exposed to emissions from biodiesel fuels

Abstract: Biodiesel or renewable diesel fuels are alternative fuels produced from vegetable oil and animal tallow that are being considered to help reduce the use of petroleum-based fuels and emissions of air pollutants including greenhouse gases. Here, we analyzed the gene expression of inflammatory marker responses and the cytochrome P450 1A1 (CYP1A1) enzyme after exposure to diesel and biodiesel emission samples generated from an in-use heavy-duty diesel vehicle. Particulate emission samples from petroleum-based Cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 48 publications
(68 reference statements)
0
19
1
Order By: Relevance
“…Here we report the first supporting evidence for the proposed biological mechanism, describing the presence, in the regulative region of the ACE-2 gene, of putative consensus motifs for the transcription factor AhR. AhR is stimulated by many endogenous and exogenous signals, including environmental pollutants such as PAHs and other noxious molecules contained in PM [ 48 , 49 , 50 ], and different ligands may specifically activate different genes’ subsets [ 51 ]. Besides the primary role in chemical defense by up-regulation of detoxifying xenobiotic enzymes, transforming toxicants into metabolites more easily excreted from the body [ 52 ], AhR acts to regulate microbial defense, organ development, immunity and inflammation [ 53 ].…”
Section: Discussionmentioning
confidence: 98%
“…Here we report the first supporting evidence for the proposed biological mechanism, describing the presence, in the regulative region of the ACE-2 gene, of putative consensus motifs for the transcription factor AhR. AhR is stimulated by many endogenous and exogenous signals, including environmental pollutants such as PAHs and other noxious molecules contained in PM [ 48 , 49 , 50 ], and different ligands may specifically activate different genes’ subsets [ 51 ]. Besides the primary role in chemical defense by up-regulation of detoxifying xenobiotic enzymes, transforming toxicants into metabolites more easily excreted from the body [ 52 ], AhR acts to regulate microbial defense, organ development, immunity and inflammation [ 53 ].…”
Section: Discussionmentioning
confidence: 98%
“…As soot and traffic-related particular matter are rich in PAHs, it has been proposed that particle-bound PAHs and their cellular sensor molecule, namely AHR, are causally involved in air pollution-induced skin pigmentation as well [2]. In fact, extracts form airborne particulate matter and diesel exhaust particles have been proven to activate AHR and downstream signaling in various cutaneous and extra-cutaneous test systems [116,117,118].…”
Section: Ahr and Extrinsic Skin Agingmentioning
confidence: 99%
“…Further, COX-2 is a proinflammatory enzyme that has been reported to be involved in inflammatory responses and cytotoxicity after PM stimulation from different sources [52,53]. Previous research has shown that urban dust or diesel exhaust induce IL-8 and COX-2 in an AhR-dependent manner in human U937-derived macrophages [54,55]. AhR is also considered to be an important receptor protein mediating the toxic responses of dioxin-like PAHs [56].…”
Section: Discussionmentioning
confidence: 99%